Equilibrium Locations in the Unconstrained Hotelling Game - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
In this paper, we try to analyse the optimal location choice in a standard game of horizontal differentiation in which firms are free to locate outside the city boundaries. It turns out that the unique Nash equilibium exhibits a finite distance between the sellers, so that the maximum differentiation principle is not confirmed. Moreover, the two symmetric Stackelberg equilibria exhibit the same degree of differentiation observed when the game is non cooperatively played within the city, except that the leader locates at the center.
Keywords: 330